6-Methoxyflavone induces S-phase arrest through the CCNA2/CDK2/p21CIP1 signaling pathway in HeLa cells. Issue 3 (1st March 2022) - Zhang, Chaihong; Quan, Yuchong; Yang, Lijuan; Bai, Yingying; Yang, Yongxiu
ABSTRACT: This study aimed to elucidate the specific anticancer mechanism of 6-methoxyflavone in HeLa cells. A total of 178 putative targets of 6-methoxyflavone were obtained from the PharmMapper database. Microarray analyses, transcriptome sequencing analyses, functional enrichment analyses, and gene set enrichment analyses were performed to preliminarily explore the roles and mechanisms of the 178 targets in cervical cancer. Cell counting kit-8, cell cycle assays, polymerase chain reactions, and western blotting were used to clarify the mechanism of action of 6-methoxyflavone. Molecular docking and noncovalent interaction analyses were performed to further confirm the mechanism of action in three-dimensional structures. Functional enrichment analyses and gene set enrichment analyses indicated that high mRNA expression of cyclin A2 (CCNA2) and cyclin-dependent kinase 2 (CDK2) stimulated cell cycle progression in cervical cancer. Cell proliferation and cycle assays, transcriptome sequencing, polymerase chain reactions, and western blotting revealed that 6-methoxyflavone inhibited HeLa cell proliferation and induced S-phase arrest via the CCNA2/CDK2/ cyclin-dependent kinase inhibitor 1A (p21CIP1) pathway. Molecular docking and noncovalent interaction analyses showed that 6-methoxyflavone had the strongest affinity toward, inhibitory effect on, and noncovalent interactions with CDK2, and that the combination of CDK2 and CCNA2 enhanced these effects. An analysis of clinical characteristics showed that 6-methoxyflavone might be related to six clinicopathological parameters of cervical cancer patients. 6-Methoxyflavone induces S-phase arrest in HeLa cells via the CCNA2/CDK2/p21CIP1 pathway. Graphical Abstract: uf0001